2021
DOI: 10.1021/acs.orglett.1c01116
|View full text |Cite
|
Sign up to set email alerts
|

DMSO as a Dual Carbon Synthon and Water as Oxygen Donor for the Construction of 1,3,5-Oxadiazines from Amidines

Abstract: A selective and efficient synthesis of diaryl 1,3,5-oxadiazines was established for the first time from simple and readily available amidines in wet DMSO. DMSO was employed as a dual carbon synthon and water offered the oxygen atom to construct the oxadiazine ring. The reaction involved two new C–N and two new C–O bond formations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Surprisingly, it was found that Cu(OTf) 2 can catalyse this reaction in a catalytic version instead of using stoichiometric amount of other activators, albeit with a low yield (14 %, entry 10). Previously, this copper salt has been used as a catalytic activator of DMSO for formylation of indoles by Chiba and co‐workers [2d,4g,5d–e] . But it was not effective enough for aminomethylenation as a catalyst in this process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, it was found that Cu(OTf) 2 can catalyse this reaction in a catalytic version instead of using stoichiometric amount of other activators, albeit with a low yield (14 %, entry 10). Previously, this copper salt has been used as a catalytic activator of DMSO for formylation of indoles by Chiba and co‐workers [2d,4g,5d–e] . But it was not effective enough for aminomethylenation as a catalyst in this process.…”
Section: Resultsmentioning
confidence: 99%
“…Activators must activate DMSO to yield active species and simultaneously avoid side reactions with starting material, other intermediates and products. In particular, catalytic activation of DMSO has been rarely reported so far [2d,4g,5d–e] . Stoichiometric amount of activator should be used in most cases of DMSO‐based reaction systems.…”
Section: Introductionmentioning
confidence: 99%
“…There are limited reports on DMSO being a dual-carbon synthon in organic transformations . Recently, Ma and co-workers described the synthesis of copper­(II)-catalyzed, Selectfluor-mediated 1,3,5-oxadiazines from amidines, DMSO, and H 2 O, where DMSO was employed as a dual-carbon synthon . In particular, Selectfluor-mediated transition metal-free transformations wherein DMSO acts as a dual-carbon synthon have not been realized yet.…”
Section: Introductionmentioning
confidence: 99%
“…Undesirable results were observed when reducing or increasing the temperature (entries 11, 12). It is worth noting that the yield of the product was decreased when changing the loading of K 2 S 2 O 8 (entries [13][14].…”
mentioning
confidence: 99%